Dolnołużycka frazeologia somatyczna - Szpila, Grzegorz (Slavia Occidentalis, 2017)
The paper discusses selected Lower Sorbian idiomatic expressions with somatic components. The author talks about somatisms and somatic phraseology in general, as well as presents different types of idiomatic motivation. A theoretical section is followed by the presentation of a corpus of somatic idioms taken from Dolnoserbsko-nimski słownik/Niedersorbisch-deutsches Wörterbuch by Manfred Starosta. The analysis of the idiomatic expressions shows how Lower Sorbian somatic phraseological units make use of somatic lexemes, as well as demonstrates the various types of motivation behind the actual senses of the examined expressions.